Heavy metals in seaweed for human consumption available in the Portuguese market - Sousa, M. (2019)
Seaweeds consumption has been increasing in European countries, including Portugal. Several studies have shown that some seaweeds species have the ability to accumulate contaminants, namely heavy metals. In particular, the presence of heavy metals in these food products can have a negative impact on the human health, and thus a systematic control of this type of food should be mandatory. In this study, five heavy metals (As, Cd, Tl, Hg, Pb) where analyzed in 16 samples of 9 species of seaweeds available in the Portuguese market for human consumption, namely Hijiki (Hizikia fusiforme), Arame (Eisenia bicyclis), Kombu (Laminaria japonica), Wakame (Undaria pinnatifida), Dulse (Palmaria palmata), seaweed spaghetti (Himanthalia elongata), seaweed lettuce (Ulva rigida) and Nori (Porphyra umbilicalis).